Living in the modern society of colonial Joseon as a patient: a study on Yi Sang’s literature focusing on diseases and physical sicknesses - Kim, Gia (International Journal of Korean Humanities and Social Sciences, 2022)
This study aims to discuss the body experiencing modern society and modernity realized through the body by analyzing the disease and physical sicknessness depicted in Yi Sang’s literature. Until now, Yi Sang’s literary research has focused on the subject’s death impulse (Thanatos) and the image of death in his works, so this study aims to present a new perspective on Yi Sang’s literature. Specifically, this paper explores works that illustrate diseases such as syphilis and tuberculosis and examines the author’s subjective consciousness. In short, this paper discusses Yi Sang’s attachment to life, which appears as a sexual impulse (Eros), by analyzing narratives that mention prostitution and syphilis among Yi Sang’s works. Meanwhile, this article reveals the author’s guilt about his inability to function properly due to syphilis. Furthermore, this paper manifests how Yi Sang presents his sick body that experiences the modern society of colonial Joseon by describing how he implements the body with tuberculosis. Therefore, in each analysis process, this study reads Yi Sang’s specific texts by referencing his various works to understand his esoteric world and literary image. Moreover, this paper reveals that the author reflects on his critical reasons for such a modern society and violent hygiene discourse in his independent literary world and identity as a patient.